A Comparative Study of the Qira’at of Imam al-Shafi’i and Imam Ibn Kathir Through the Riwayahs of al-Bazzi and Qunbul - Mohammad Anas Mubarok; Fitrotul Maulidina; Mohammad Samsul Ulum; Mohammad Yahya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Studies on the qira’at of Imam al-Shafi’i remain fragmented and lack systematic comparison with the canonical riwayat of Ibn Kathir. This gap is particularly significant given that the Shafi’i madhhab predominates in Indonesia and Southeast Asia. This study presents a systematic comparative analysis of the qira’at of Imam al-Shafi’i (d. 204 AH) and those of Imam Ibn Kathir in the riwayahs of al-Bazzi and Qunbul at both the usul and farsh al-huruf levels, using a qualitative descriptive-comparative method (al-manhaj al-wasfi al-muqaran). Data were drawn primarily from al-Kamil fi al-Qira’at by al-Hudhali and At-Tariq al-Munir by Damrah. The findings show that at the usul level, al-Shafi’i agrees with both rawis on 8 of 13 principles, while differences appear in mad wajib muttasil and idgham nun sakinah. At the farsh level, 51.9% of 77 entries show al-Bazzi and Qunbul agreeing but diverging from al-Shafi’i, 27.3% show exclusive conformity with al-Bazzi, and 16.9% with Qunbul. All three transmission chains converge at Isma’il ibn ‘Abdillah al-Qast, confirming that al-Shafi’i possessed an independent recitation tradition with a sahih sanad rooted in the Makkah qira’at.